2017
DOI: 10.3847/1538-4357/aa8d15
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR Hard X-Ray Observation of the Gamma-Ray Binary Candidate HESS J1832–093

Abstract: We present a hard X-ray observation of the TeV gamma-ray binary candidate HESSJ1832−093, which is coincident with the supernova remnant G22.7−0.2,using the Nuclear Spectroscopic Telescope Array. Nonthermal X-ray emission from XMMUJ183245−0921539, the X-ray source associated with HESSJ1832−093, is detected up to ∼30keV and is well-described by an absorbed power-law model with a best-fit photon indexA re-analysis of archival Chandra and XMM-Newton data finds that the long-term X-ray flux increase of XMMUJ1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
(105 reference statements)
5
12
0
Order By: Relevance
“…Since G22.7−0.2 is in a complex region with MCs, H II regions and the GLIMPSE9 stellar cluster (Su et al 2014), we consider the possibility of having a binary object related with those systems, thus at a distance of d = 4.4 ± 0.4 kpc. Assuming this distance and using the IR magnitudes from the literature of 2MASS J18324516−0921545, Mori et al (2017) derived a spectral type between B8V and B1.5V, fully compatible with the stars found in other γ-ray binaries (Dubus 2013). However, this result is only a lower limit since local dust absorption would increase their optical extinction (A V = 7.7).…”
Section: On the Optical Counterpart Issuesupporting
confidence: 67%
“…Since G22.7−0.2 is in a complex region with MCs, H II regions and the GLIMPSE9 stellar cluster (Su et al 2014), we consider the possibility of having a binary object related with those systems, thus at a distance of d = 4.4 ± 0.4 kpc. Assuming this distance and using the IR magnitudes from the literature of 2MASS J18324516−0921545, Mori et al (2017) derived a spectral type between B8V and B1.5V, fully compatible with the stars found in other γ-ray binaries (Dubus 2013). However, this result is only a lower limit since local dust absorption would increase their optical extinction (A V = 7.7).…”
Section: On the Optical Counterpart Issuesupporting
confidence: 67%
“…To the west of HESS J1834−087 is HESS J1832−093. Recent observations, strongly indicate a non-accreting binary origin for this gamma-ray emission (Eger et al 2016;Mori et al 2017). This is contrasted with initial investigations which suggested a possible association with the SNR G22.7−0.2 (HESS Collaboration et al 2015).…”
Section: The W41 Region and Hess J1832−085mentioning
confidence: 81%
“…Recently Mori et al (2017) reported on a NuSTAR X-ray observation of the field containing HESS J1832-093 and a reanalysis of the archival Chandra and XMM-Newton data. The data reanalysis does not confirm the same level of flux variation reported in previous work.…”
Section: Hess J1832-093mentioning
confidence: 99%